2015
DOI: 10.1007/s11837-015-1562-x
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Response of Two Nanoscale Bainite Composite-Like Structures

Abstract: The present work is concerned with the study of the relationship between microstructure and ductility of nanostructured bainite. The tensile behavior of two steels treated at the same temperature during different times has been analyzed. Special attention has been paid to the role that the retained austenite mechanical stability plays in enhancing the ductility through its contribution to the work-hardening and the damage resistance of these materials. The results have shown that the relative mechanical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 87 publications
(110 reference statements)
2
27
0
Order By: Relevance
“…(2) Two austenite C contents, 0.6 and 1 wt %. This covers a range of concentrations in good agreement with the values detected by XRD for the nanobainitic structures examined in the mentioned reference [54].…”
Section: Retained Austenite Evolution and Mechanical Partitioningsupporting
confidence: 88%
See 3 more Smart Citations
“…(2) Two austenite C contents, 0.6 and 1 wt %. This covers a range of concentrations in good agreement with the values detected by XRD for the nanobainitic structures examined in the mentioned reference [54].…”
Section: Retained Austenite Evolution and Mechanical Partitioningsupporting
confidence: 88%
“…There is no correlation between the elongation and the strength of the material (yield strength and UTS, separately) either, as seen in Figure 5b,c, with data from reference [53]. On the other hand, it has been reported that the samples with a high ductility present a stronger damage resistance [54]. This can be evaluated with another parameter, UTS·e t , , which is a measure of the toughness, as in Figure 5d, with data from reference [53], where the correlation is confirmed.…”
Section: Ductility: Work-hardening and Fracture Mechanisms In Nanostrmentioning
confidence: 59%
See 2 more Smart Citations
“…One of the most effective approaches to increase both strain hardening and ductility is the transformation-induced plasticity, i.e. the TRIP effect, which is observed in dual-/multi-phase steels [11e13,16e18], TRIP steels [11,12,19e23], bainite steels [15,24], etc. In these steels, the phase-specific deformation mechanism takes effect at different stress or strain levels and therefore, the global plastic response is composite-like, which critically depends on the evolution of stress transfer and dynamic strain partitioning among different phases [11,12].…”
Section: Introductionmentioning
confidence: 99%